1999
DOI: 10.1149/1.1392011
|View full text |Cite
|
Sign up to set email alerts
|

An In Situ X‐Ray Absorption Spectroscopic Study of Charged Li ( 1 − z ) Ni ( 1 + z )  O 2 Cathode Material

Abstract: We have measured in situ the Ni K‐edge X‐ray absorption spectra of Lifalse(1−zfalse)Nifalse(1+zfalse)O2 cathode material charged in a nonaqueous cell. The material was charged to various states of charge (i.e., Li content) which corresponded to x = 0.0, 0.12, 0.24, 0.37, 0.49, and 0.86 in Lifalse(1−x−zfalse)Nifalse(1+zfalse)O2 . We have determined variations in the Ni‒O and Ni‒Ni coordination numbers, bond lengths, and local disorders as well as the Ni K‐edge energies as a function of Li content. We show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
69
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
(56 reference statements)
12
69
0
Order By: Relevance
“…This is consistent with recent theoretical work [36][37][38]. Not all experimental work has been interpreted in this way [39][40][41][42][43], but measurements of the O K-edge do show such behavior [34,[44][45][46][47]. From measurements of the Ni and Co L 2,3 edges, we found that there may be a small change in 3d occupany at Ni atoms, but not at Co atoms in our samples of LiNi 0.8 Co 0.2 O 2 [34].…”
Section: Valence Changes With Lithiation In Licoosupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with recent theoretical work [36][37][38]. Not all experimental work has been interpreted in this way [39][40][41][42][43], but measurements of the O K-edge do show such behavior [34,[44][45][46][47]. From measurements of the Ni and Co L 2,3 edges, we found that there may be a small change in 3d occupany at Ni atoms, but not at Co atoms in our samples of LiNi 0.8 Co 0.2 O 2 [34].…”
Section: Valence Changes With Lithiation In Licoosupporting
confidence: 90%
“…* We find no evidence of special structures at compositions x=0.5 and x=0.75 as reported by Delacourt, et al [41], and they have no evidence that the new materials at these compositions are anything other than disordered phases [42].…”
supporting
confidence: 54%
“…LiCoO 2 does, however, suffer from relatively high cost [10] and environmental processing and disposal problems [11]. For this reason, the related materials LiNiO 2 and LiNi 1−x Co x O 2 have been studied as potential substitutes for the lithium ion anode [12], [13], [14], [15], [16], [17] and [18]. LiCoO 2 and "hexagonal" LiNiO 2 can be idealized as cubic (rocksalt) structures in which planes of the much smaller lithium ions alternate with cobalt or nickel ions along the 〈 1 1 1〉 direction ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has been driven by the success of the lithiated transition-metal oxides as cathodes in rechargeable lithium batteries. A number of x-ray absorption and EELS experiments have been performed to investigate charge compensation during electrochemical cycling of lithium 2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19 17 and it is unclear how much charge is transferred to each transition-metal ion. It is our contention that changes in the transitionmetal valence can be measured quantitatively using the transition-metal white lines.…”
Section: Introductionmentioning
confidence: 99%